Pilotní studie ročního režimu pohybové aktivity gymnaziálních studentek [Variability of year-round physical activity in high school girls - pilot study] - Marek Pelcl; František Chmelík; Jana Vašíčková; Jana Pelclová; Karel Frömel (Palacký University Olomouc, 2008)
Tato studie analyzuje výsledky výzkumu u devíti gymnaziálních dívek, které dobrovolně celý školní rok 2005-06 nosily krokoměry k monitorování pohybové aktivity a její variability v průběhu jejich školní docházky a volného času. Korigovaná data byla zpracována opakovanou analýzou rozptylu a zjištěny byly významné rozdíly mezi dny v týdnu, měsíci, dny s vyučovacími jednotkami tělesné výchovy a bez tělesné výchovy a ročními obdobími. [The adolescent period seems to be critical in age-related decline of physical activity. To infl uence physical activity behavior in children and youth, it is necessary to determine factors aff ecting physical activity which are related to seasonal, monthly or weekly period. Therefore, the purpose of this study is to collect one year pedometer self-monitoring data to fi nd out the year-round variability of physical activity in high school girls. Nine volunteering girls from a high school participated in this study. Girls were asked to wear pedometer at their waist during each day of one year and record steps per day and daily behavior. We obtained 2118 person-day, each girl recorded 303 days. The days with lowest number of steps were Saturday and Sunday. The highest number of steps was obtained on days with regular physical education lesson - Wednesday. The month with the lowest average number steps/day was February and the average number steps/day was the highest in June. Although this study has several limitations (e.g. low sample size), the variability in year-round physical activity has been found across days and autumn, winter, and spring months.]